O que pode o corpo do trabalhador? compostagens entre subjetividade, cuidado e risco - Monteiro, Fabiana Ribeiro (2017)
Thinking about the problematization of the working subject requires questioning about the forms that social existence can take. This premise leads us to analyze the relations between politics and corporeity, since the fabrication of a body is a way of experiencing time, and politics is not simply a question of a circuit of goods and riches, ways of regulating inequalities socioeconomic variables. The body is the instrument through which our struggles, our risks, our affective implication in the community pass. By serving as a kind of colonizing catch and investing in individual neoliberalist ownership, historical, economic, cultural, linguistic, and other aspects that are (re) produced in ways of life are updated. These experiences can be perpetuated in a distance between the bodies or in the production of encounters as spaces of rupture to the current system. Here we were interested in following another experience of knowledge, possible and real in the process of the production of subjectivity. Stagnating it means coagulating fissures, accidents, mutations, and therefore, committing ourselves to the eternal search for the best model, pointing guilty, judging procedures, speaking on behalf of others, denouncing "irregularities", tutelary the object